Effect of eating alone on dietary practice in community-dwelling elderly in Japan - Ishida, Akira; Ishida, Emik (Progress in Nutrition, 2021)
Objective: Our study aimed to examine whether eating alone has negative effects on dietary practices among community-dwelling elderly in Japan, while considering gender and cohabitation status differences. Methodology: Individual data for adults ≥65 years old was obtained from two nationwide Surveys of Attitudes towards Food and Nutrition Education (Shokuiku) conducted by the Ministry of Agriculture, Forestry and Fisheries in 2016 and 2017. Ordered logit models with various dietary practices as dependent variables were developed. Findings: Single men were least likely to attempt to adopt a healthy dietary lifestyle, actually eat a balanced diet, avoid too much salt, and eat many vegetables and fruit, followed by men living with their families and eating alone. Elderly individuals with higher self-reported financial means were more likely to attempt to adopt a healthy dietary lifestyle and actually eat balanced meals. However, the marginal effects at means were significantly smaller than those of the dummies for single men and men living with their families and eating alone. Additionally, knowledge of food safety was likely to increase consciousness about healthy dietary habits, but did not affect actual dietary practice among the elderly. Taken together, our data suggest that eating alone may be a stronger determinant of actual dietary practices than living alone. Originality: To our knowledge, the gender- and cohabitation status-dependent effect of eating alone on dietary practices among community-dwelling elderly has so far attracted little attention. Our study attempted to examine whether eating alone has a negative effect on dietary practices among community-dwelling elderly, while considering gender and cohabitation status differences.